If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(-4 + 2v) = -20 + v (-4 * -4 + 2v * -4) = -20 + v (16 + -8v) = -20 + v Solving 16 + -8v = -20 + v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-1v' to each side of the equation. 16 + -8v + -1v = -20 + v + -1v Combine like terms: -8v + -1v = -9v 16 + -9v = -20 + v + -1v Combine like terms: v + -1v = 0 16 + -9v = -20 + 0 16 + -9v = -20 Add '-16' to each side of the equation. 16 + -16 + -9v = -20 + -16 Combine like terms: 16 + -16 = 0 0 + -9v = -20 + -16 -9v = -20 + -16 Combine like terms: -20 + -16 = -36 -9v = -36 Divide each side by '-9'. v = 4 Simplifying v = 4
| 3k^2+12k-29=7 | | 1/3x+2/6=5x-2/3 | | (7x+33)=(9x+7) | | 9=2r-5 | | 2x-29=93 | | 23x+5x=2x | | -4(-2x+2)+8x=-(5x+7) | | X-47=12 | | X+3=3+2(2+3x)-5x | | x+x-30=180 | | 6(6x-11)=54x | | b=60+(15+7) | | -5d=20 | | x-30=180 | | (8x-4)+(10x+6)= | | 5x-3=-3x-1 | | (X-7)+12=20 | | 7a-18=-3(-3+3)+7a | | x+15=4x-36 | | -40=b-51 | | H=7+27t-16t^2 | | x*15=4x-36 | | 6(x-11)=54x | | -9r-18r-3r=-12 | | 28=4s+r-s | | 4(3x+3)=3(5x+0.5) | | 1204.2528=2*3.14*6.8*6.8+2*3.14*6.8*h | | 4a-3a=a | | 0=x^2+2x+420 | | 4p+2=-3p+5p | | 4x+0.5= | | h=-2t^2+8t |